Environmental tax reform in a small open economy with structural unemployment - Bertil Holmlund; Ann-Sofie Kolm (Fondazione Eni Enrico Mattei (FEEM), 1997)
The paper examines the effects of an environmental tax reform in a model of a small open economy with decentralised wage bargaining and monopolistically competitive firms. The economy includes a tradable sector as well as a non-tradable sector and features unemployment in general equilibrium. Firms in both sectors use labour and an imported polluting factor of production ("energy"). A tax on energy, recycled to reduce the payroll tax, will in general affect equilibrium unemployment in this economy. The effect works through a reallocation of employment from the tradable to the non-tradable sector. Total employment increases if workers in the tradable sector receive a wage premium relative to workers in the non-tradable sector. The sectoral relative wage is determined by the relative bargaining power of the unions and by parameters of preferences and technology. Parameterised versions of the model suggest that the tax reform has small effects on employment and that it typically reduces real GDP.
Keywords: H20; J51; J64; Q43; 330; Environmental tax reform; wage bargaining; equilibrium; unemployment